LINGUOPRAGMATIC ANALYSIS OF SOME WORD COMBINATIONS - Mahliyo PARDAYEVA (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This scientific article comparatively analyzed the linguo-pragmatic analysis of word combinations on the example of the most used T. Dreiser's work "Sister Carrie" and also substantive word combinations in some works.